EVIDENCE BASED CASE REPORT (EBCR) PENGARUH PIJAT EFFLEURAGE TERHADAP PENURUNAN NYERI PERSALINAN KALA I (Politeknik Kesehatan Kemenkes Bandung, 2022)
Background: Childbirth is a happy event for every woman, but during the delivery process every woman will feel pain and that is a physiological and psychological thing. Every woman has different pain. The causes of labor pain result from several factors such as uterine muscle contractions, pelvic floor muscle strain and psychological conditions. One of the non-pharmacological methods that can be used to reduce labor pain is natural effleurage massage. Purpose: This Evidence Based Case Report (EBCR) aims to determine the effect of effleurage massage on labor pain. Method: The Evidence Based Case Report (EBCR) method uses article searches regarding the effect of effleurage massage on Google Scholar and Garuda. Result: There were 2 quasi-experimental design articles by Herinawati, et al and Magfirah that met the inclusion and exclusion criteria and then had previously been screened and the assessment of maternal pain was assessed using the Numeric Rating Scale (NRS). The author applies effleurage massage to women in labor during the active phase I, before the massage the pain experienced by the mother is included in the moderate pain category with a value of 6, after being given effleurage massage for 20 minutes there is a decrease in pain to a mild pain scale with a value of 3. Conclusions: This proves the existence the effect of effleurage massage on labor pain in the first stage of the active phase